AN ANALYSIS OF STUDENTS' TRANSLATIONS OF POLITICAL TEXTS (A CASE STUDY OF THE 7TH SEMESTER STUDENTS OF ENGLISH DEPARTMENT IN UPI)" - Cucu Hendrayani, - (2009)
This research entitled "An Analysis of Students' Translations of Political Texts (A Case Study of the 7th Semester Students of English Department in UPI)" was aimed at analyzing the translation procedures used by the respondents in translating political texts and the difficulties faced by them in translating it. In this research, the theory used in analyzing the translation procedures is the one proposed by Newmark (1988). This research applied descriptive qualitative method by employing the following techniques. First, the writer chose randomly four political texts taken from Political Education by Robert Brownhill & Patricia Smart as the instrument and then decided 20 students as the respondents. Second, she had the respondents translate the texts into Indonesian and then spread the questionnaires to them. Third, the writer analyzed the texts translated by the respondents in terms of the procedures of translation. Fourth, to find the difficulties faced by the respondents in translating those texts, the writer analyzed and transcribed the collected data from questionnaires. Finally, she drew conclusions based on the data gained. The writer found out that literal is the most common procedure used by the respondents in translating political texts, with its percentage is 33.4 %. However, there were also the other kinds of procedures applied by them, namely naturalization (21.9 %), paraphrase (15.8 %), reduction (10.8 %), shift (6.9 %), expansion (4.3 %), couplet (1.6 %), transference (1.3 %), synonymy (0.7 %), and addition (0.1 %). Meanwhile, the rest of the translations are mistranslated and not translated by the respondents. Based on the respondents' answers and the data analysis, the main difficulty faced by the respondents in translating the political texts was to translate the political terminologies which were unfamiliar for them. Besides, the other difficulties faced by them were to find the equivalent words in target language, to adjust and select the most proper word in target language, to understand its sentence structure, to translate the phrases, and to make a sensible meaning from the political terms.